Colonial legacy as a source and a problem in South-South Cooperation: The Case of Brazil - Elena Borisovna Pavlova (Vestnik RUDN. International Relations, 2017)
The aim of this article is to identify the key narratives of colonial legacy as nodal points in the articulation of the Brazilian agenda in the South-South cooperation. Brazil’s aspirations for regional leadership and attempts to increase its international prestige are analyzed in a constructivist framework. Most importantly, our theoretical reasoning departs from the constructivist take on the agent-structure debate, proposed by A. Wendt in 1987. This approach, firstly, helps to clarify the main difficulties which Brazil faced in Latin America and to examine Brazilian efforts to overcome colonial legacy in order to secure regional leadership, one of the principal goals of its foreign policy. Secondly, colonial legacy can be seen as an unconditional source for the geographical expansion of Brazil’s influence and the increasing the number if its allies by means of the South-South cooperation. Thirdly, we demonstrate the very complex relationship on the structural level between the BRICS project and the problem of colonial legacy. Using the example of Brazil as a state which, on the one hand, has not been able to overcome the postcolonial complex, and on the other, is actively performing political rituals aimed at demonstrating its increasing power, we can more clearly outline the possibilities and limitations inherent in the structure of contemporary international system. Finally, this research suggests that BRICS, a group that claims to articulate the principles of the new world order, more beneficial for the states of the South, has limited chances to succeed with that mission.